Preparation method of pectin-cellulose composite bioplastic based on fruit peel waste
Through the separation and in-situ self-assembly principle of pectin and cellulose in the peel cell wall, combined with the action of citric acid, pectin-cellulose composite bioplastics are prepared, which solves the problem of converting peel waste into high-performance bioplastics, and realizes the high mechanical properties and degradability of bioplastics, and has the potential to replace petrochemical plastics.
Patent Information
- Application Number
- CN202411856625.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-17
AI Technical Summary
In the prior art, fruit peel waste is difficult to directly convert into high-performance and degradable bioplastics, and the mechanical and processing properties of bioplastics are poor, difficult to recycle and reuse, and chemical reagents are required.
Through the separation of pectin and cellulose in the cell wall of the peel and the in-situ self-assembly principle, citric acid is used as a bridge to form a stable structure to prepare pectin-cellulose composite bioplastics. The method includes the steps of enzymatic treatment of the peel, wall breaking treatment, dialysis, concentration and ultrasonic dispersion.
The prepared bioplastics have high mechanical strength and toughness, are biosafe, degradable, processable and recyclable properties, and can replace petrochemical plastics, which are particularly suitable for the food packaging field.
Smart Images

Figure CN119751712A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of harmless treatment and processing application of fruit peel waste, and in particular to a pectin-cellulose composite bioplastic based on fruit peel waste and a preparation method thereof. Background Art
[0002] Petrochemical plastics are widely used in the food industry due to their low cost and ideal mechanical and processing properties. However, these plastics are often difficult to degrade, and they accumulate in large quantities in nature, causing serious damage to the environment and ecosystem. More seriously, the micro-nanoplastics generated by the use of plastics have a great risk of migrating into food, posing a major threat to human health. There is increasing evidence that the widespread use of plastics in direct contact with food, such as packaging and tableware, has exacerbated the migration of micro- and nano-plastics into food. Therefore, the development of biodegradable bioplastics using safe and renewable natural biopolymers (e.g., lignocellulose and pectin) to replace traditional petrochemical plastics in the food industry has received widespread attention and interest.
[0003] Fruit peels and some other agricultural wastes can be considered as good sources of these natural biopolymers and have the potential to develop biodegradable bioplastics. According to statistics, the food industry generates more than 492 million tons of fruit and vegetable waste each year. These organic solid wastes are highly fermentable, and improper management often poses serious threats to the environment and human health, including water pollution, eutrophication, and greenhouse gas emissions. In addition, the current common waste management practices (especially incineration and landfill) often do not take into account the high-value utilization of fruit wastes, making it difficult to generate additional economic benefits. Therefore, from the perspectives of environment, economy, resource management and sustainable development, converting these biomass wastes into valuable biodegradable plastics through innovative methods can not only solve the current serious plastic pollution and inefficient management of organic waste, but also open up a new path for sustainable materials science, which is of great strategic significance.
[0004] However, it is not an easy task to directly convert fruit peel waste into bioplastics. There are currently few studies on the use of fruit peel waste to prepare bioplastics, and the reported bioplastics generally exhibit poor properties, such as low mechanical strength and flexibility. In addition, due to the lack of effective energy dissipation and molecular fluidity, the reprocessability of bioplastic films prepared using natural polymers is usually unsatisfactory, which seriously limits their further application. Therefore, it is challenging and meaningful to directly produce high-performance and balanced degradable bioplastics using fruit peels in a simple and sustainable way. Summary of the invention
[0005] In order to solve the problems of low efficiency in organic food waste management and plastic environmental pollution in the prior art, as well as the problems of poor mechanical properties, poor processing properties, difficulty in recycling and reuse of current bioplastics, and the need to add chemical reagents such as film formers and plasticizers, the present invention proposes a pectin-cellulose composite bioplastic based on peel waste and a preparation method thereof, which specifically utilizes the separation of pectin and cellulose in the peel cell wall and the principle of in-situ self-assembly to make them tightly entangled to form a stable structure similar to a carboxylic acid dimer. The prepared bioplastic has high mechanical strength and toughness, and has the properties of biosafety, degradability, processability and recyclability, and has great potential to replace petrochemical plastic products, especially in the field of food packaging.
[0006] The present invention provides a method for preparing pectin-cellulose composite bioplastic based on peel waste, comprising the following steps: 1) Dry and crush the peel; 2) Mix the peel powder with water, perform enzymatic hydrolysis, and centrifuge to obtain the precipitate; 3) mixing the precipitate obtained in step 2) with water, adjusting the pH with a saturated citric acid solution, breaking the cell wall under high pressure, and then magnetically stirring at 65-95°C for 2-4 h; 4) cooling the mixture obtained in step 3), and placing it in a dialysis bag for dialysis; 5) concentrating the dialyzed mixed solution obtained in step 4), dispersing by ultrasonication, and stirring until uniform to obtain a pectin-cellulose composite film-forming slurry; 6) Degas the slurry obtained in step 5), pour it evenly onto a glass plate, evaporate the water at room temperature, and peel it off to obtain bioplastic.
[0007] Preferably, in step 1), the peel is crushed and then passed through a 200-mesh sieve; the present invention uses the peel as a raw material, utilizes its pectin and cellulose to separate and self-assemble in situ, and obtains a pectin-cellulose composite bioplastic. The peel is selected from one of citrus peel, watermelon peel, cantaloupe peel, pineapple peel, apple peel and residue.
[0008] Preferably, in step 2), the peel powder is mixed with water in a ratio of 1 g: (15-30) mL, and then 0.15%-0.25% of the weight of the peel is added with hemicellulase, and the mixture is shaken at 40°C for 15-30 min, followed by centrifugation at 5000-6000 rpm to obtain a precipitate; the activity of the hemicellulase used is ≥ 200 unit / mg solid; and it is further preferred that the peel powder is mixed with water in a ratio of 1 g: 20 mL.
[0009] Hemicellulase enzymatic hydrolysis can remove the hemicellulose components in the peel, which is beneficial for screening and obtaining its main pectin and cellulose components.
[0010] Preferably, in step 3), the precipitate is mixed with water in a ratio of 1 g: (15-30) mL, and then the pH is adjusted to between 1.8 and 2.2 using saturated citric acid, and the pressure of the high pressure environment is 2.0-3.0 MPa.
[0011] Preferably, in step 3), the cell wall breaking treatment is ultrasonic-microwave synergistic treatment, the microwave power is 200-500W, the ultrasonic power is 200-400W, and the treatment time is 10-20min; Under the microwave-high pressure synergistic ultrasonic microwave environment, the peel cell wall is rapidly deconstructed, and the pectin and cellulose therein are exposed to the acid solution, which accelerates the separation of pectin and cellulose.
[0012] Preferably, in step 4), the molecular cutoff of the dialysis bag is 3.5-6.0 KDa, the dialysis time is 24-48 hours, and the water is changed every 6-8 hours; Under the action of dialysis, oligosaccharides with smaller molecular weight and some other impurities including most of the citric acid in the mixed solution can be dialyzed out, while pectin and cellulose with larger molecular weight are retained, which provides a basis for further in situ polymerization / cross-linking of pectin and cellulose to prepare pectin-cellulose composite bioplastics.
[0013] Preferably, in step 5), the concentration degree of the mixed solution after dialysis needs to be determined based on its pectin and cellulose content. Specifically, every 10g of peel raw material should be concentrated to 100mL. If the concentrated volume is too low, the pectin-cellulose composite content ratio is too high, which will cause partial acoustic cavitation during the ultrasonic process in step 5) and agglomeration of polymers near the ultrasonic probe, affecting the energy transfer and making it difficult to evenly disperse the pectin-cellulose composite. This uneven slurry cannot be used for film laying. If it is not concentrated or the concentrated volume is large, the pectin-cellulose composite concentration in the slurry will be reduced, resulting in poor film formation.
[0014] Preferably, in step 5), the ultrasonic power of the ultrasonic dispersion is 200-500W, the ultrasonic time is 5-10min, and then stirred until completely distributed; ultrasonic treatment enables the pectin-cellulose to be quickly and evenly dispersed in water to form a uniformly distributed slurry for the production of pectin-cellulose composite bioplastic film.
[0015] Preferably, in step 6), the vacuum degree during degassing is -0.1 MPa, and the slurry is poured onto a glass plate with a thickness of 0.3-0.5 cm. Too thin or too thick is not conducive to the stable formation of a film; the drying condition is to evaporate the water naturally at room temperature.
[0016] The present invention first removes the hemicellulose component by enzymatic treatment of the peel, then completes the crushing of the peel cell wall and the separation of pectin and cellulose by microwave ultrasound-assisted thermal acid treatment under high pressure, and then uses a dialysis bag to remove oligosaccharides and other impurities with smaller molecular weights including most of citric acid, retaining pectin and cellulose, and preliminarily obtains a pectin-cellulose composite mixed liquid, and obtains a pectin-cellulose composite slurry that can be used for bioplastic production after concentration and ultrasound treatment. Single-component citrus peel cellulose and pectin are difficult to stably form a film without adding other substances, or the performance after film formation is very poor, such as high brittleness and low mechanical strength.
[0017] The use of citric acid accelerates the separation of pectin and cellulose, while the small amount of citric acid remaining after dialysis plays a connecting role, allowing pectin and cellulose to form a stable structure to form bioplastics.
[0018] Pectin-cellulose composite bioplastics were prepared by the above method. During the preparation process, other impurities (hemicellulose and some oligosaccharides and polysaccharides) were removed in the subsequent dialysis step by high-pressure microwave ultrasonic treatment and hot acid treatment.
[0019] The present invention utilizes the separation and in-situ self-assembly principle of pectin and cellulose in the cell wall of the fruit peel to make them tightly entangled to form a stable structure similar to carboxylic acid dimer. The prepared bioplastic has high mechanical strength and toughness, and has the properties of biosafety, degradability, processability and recyclability, and has great potential to replace petrochemical plastic products (especially in the field of food packaging).
[0020] The peel-based pectin-cellulose composite bioplastic and the preparation method thereof provided by the present invention have the following advantages and beneficial effects: (1) The present invention makes maximum use of the peel waste, which not only avoids the environmental and ecological damage caused by it, but also improves the application value of the peel waste; (2) The obtained bioplastic has high mechanical strength (46.3MPa) and toughness (5.1MJ / m 3 ), and can be completely degraded (within one month); (3) The obtained bioplastics are recyclable. After the use cycle ends, the bioplastics can be processed again to form new bioplastics after simple treatment; (4) The method used does not require other chemical reagents such as film-forming agents and plasticizers. It is safe, green, simple and easy to operate, low-cost, and easy to achieve sustainable mass production; (5) The prepared bioplastic is safe and non-toxic and can be used as a substitute for petrochemical plastics, especially in the field of food packaging. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1Flow chart for preparing bioplastics for the present invention; Figure 2 An example of the output of fruit peel waste for preparing bioplastics in the present invention, the formation mechanism of bioplastics, a comparison of performance with other plastics, and a schematic diagram of large-scale production; Figure 3 Density functional theory (DFT) of the bioplastic production process prepared in Example 1, wherein (a) is the DFT simulation between pectin, cellulose and citric acid; (b) is the possible structure formed by pectin, citric acid and cellulose inferred based on the DFT simulation; Figure 4 The images of the load-bearing, plasticity, and folding properties of the bioplastic prepared in Example 1; Figure 5 The process for preparing bioplastics according to the present invention is universally verified in various fruit peels, including (a) watermelon peel, (b) pineapple peel, (c) apple pomace, and (d) cantaloupe peel; Figure 6 The weldability, processability and recyclability of the bioplastic prepared in Example 1 under the action of water; Figure 7 Biological toxicity test of the bioplastic prepared in Example 1; Figure 8 The biodegradability of the bioplastic prepared in Example 1 in soil and natural environment. DETAILED DESCRIPTION
[0022] The embodiments of the present invention will be further described in detail by examples. It is necessary to point out that the following examples are only used to further illustrate the present invention, and the embodiments of the present invention are not limited thereto. Some non-essential adjustments and improvements made by people familiar with the relevant fields according to the above invention scheme still belong to the protection scope of the present invention.
[0023] The peels used in the protocol were collected from the local market; the remaining substances and reagents were all commercially available products unless otherwise specified.
[0024] Example 1 A method for preparing pectin-cellulose composite bioplastic based on fruit peel waste comprises the following steps: Select citrus peel, wash and dry it, and crush it through a 200 mesh sieve to obtain citrus peel powder. Weigh 10 g of citrus peel powder, mix it with water at a ratio of 1 g:20 mL, add 15 mg of hemicellulase (≥200 unit / mg solid), and incubate it at 40°C in a water bath constant temperature oscillator for 20 min. Then centrifuge to obtain the precipitate, mix it with water at a ratio of 1 g:20 mL, and then use saturated citric acid solution to adjust the pH of the mixture to 2, place it in a high pressure environment of 2.0 MPa, and treat it with ultrasound and microwave synergy for 10 min (microwave power: 500 W; ultrasonic power: 300 W), followed by magnetic stirring at 95°C for 2.5 h. After cooling, the mixture was dialyzed in a 3.5 KDa dialysis bag for 48 h, and then the dialyzed mixture was concentrated to 100 mL. The concentrated mixed solution was ultrasonically treated at 300 W for 5 min to form a pectin-cellulose composite film-forming slurry, which was then magnetically stirred until completely uniform. After degassing, it was poured onto a glass plate of appropriate size (slurry thickness was about 0.5 cm), dried at room temperature, and the film was peeled off.
[0025] Example 2 A method for preparing pectin-cellulose composite bioplastic based on fruit peel waste comprises the following steps: Select citrus peel, wash and dry it, crush it through a 200 mesh sieve to obtain citrus peel powder. Weigh 10 g of citrus peel powder, mix it with water at a ratio of 1 g:20 mL, add 15 mg of hemicellulase (≥200 unit / mg solid), and incubate it at 40°C in a water bath constant temperature oscillator for 20 min. Then centrifuge to obtain the precipitate, mix it with water at a ratio of 1 g:50 mL, and then use saturated citric acid solution to adjust the pH of the mixture to 2, place it in a high pressure environment of 2.0 MPa, and treat it with ultrasound and microwave for 10 min (microwave power: 500 W; ultrasonic power: 300 W), followed by magnetic stirring at 95°C for 2.5 h. After cooling, the mixture was dialyzed in a 3.5 KDa dialysis bag for 48 h, and then the dialyzed mixture was concentrated to 100 mL. The concentrated mixed solution was ultrasonically treated at 300 W for 5 min to form a pectin-cellulose composite film-forming slurry, which was then magnetically stirred until completely uniform. After degassing, it was poured onto a glass plate of appropriate size (slurry thickness was about 0.5 cm), dried at room temperature, and the film was peeled off.
[0026] Example 3 A method for preparing pectin-cellulose composite bioplastic based on fruit peel waste comprises the following steps: Select citrus peel, wash and dry it, and crush it through a 200 mesh sieve to obtain citrus peel powder. Weigh 10 g of citrus peel powder, mix it with water at a ratio of 1 g:20 mL, add 15 mg of hemicellulase (≥200 unit / mg solid), and incubate it at 40°C in a water bath constant temperature oscillator for 20 min. Then centrifuge to obtain the precipitate, mix it with water at a ratio of 1 g:20 mL, and then use saturated citric acid solution to adjust the pH of the mixture to 2, place it in a high pressure environment of 2.0 MPa, and treat it with ultrasonic microwave synergy for 5 min (microwave power: 400 W; ultrasonic power: 200 W), followed by magnetic stirring at 95°C for 2.5 h. After cooling, the mixture was dialyzed in a 3.5 KDa dialysis bag for 48 h, and then the dialyzed mixture was concentrated to 100 mL. The concentrated mixed solution was ultrasonically treated at 300 W for 5 min to form a pectin-cellulose composite film-forming slurry, which was then magnetically stirred until completely uniform. After degassing, it was poured onto a glass plate of appropriate size (slurry thickness was about 0.5 cm), dried at room temperature, and the film was peeled off.
[0027] Example 4 A method for preparing pectin-cellulose composite bioplastic based on fruit peel waste comprises the following steps: Citrus peels were selected, washed, dried, and crushed through a 200-mesh sieve to obtain citrus peel powder. 10 g of citrus peel powder was weighed, mixed with water at a ratio of 1 g:20 mL, 15 mg of hemicellulase (≥200 unit / mg solid) was added, and incubated at 40°C in a water bath constant temperature oscillator for 20 min. The precipitate was then centrifuged and mixed with water at a ratio of 1 g:20 mL, and then the pH of the mixture was adjusted to 2 with a saturated citric acid solution, placed in a high pressure environment of 2.0 MPa, and ultrasonic microwave synergistically treated for 10 min (microwave power: 500 W; ultrasonic power: 300 W) and then magnetically stirred at 95°C for 2.5 h. After cooling, the mixture was dialyzed in a 6.0 KDa dialysis bag for 36 h, and then the dialyzed mixture was concentrated to 100 mL. The concentrated mixed solution was ultrasonically treated at 300 W for 5 min to form a pectin-cellulose composite film-forming slurry, which was then magnetically stirred until completely uniform. After degassing, it was poured onto a glass plate of appropriate size (slurry thickness was about 0.5 cm), dried at room temperature, and the film was peeled off.
[0028] Example 5 A method for preparing pectin-cellulose composite bioplastic based on fruit peel waste comprises the following steps: Select citrus peel, wash and dry it, crush it through a 200 mesh sieve to obtain citrus peel powder. Weigh 10 g of citrus peel powder, mix it with water at a ratio of 1 g:20 mL, add 15 mg of hemicellulase (≥200 unit / mg solid), and incubate it at 40°C in a water bath constant temperature oscillator for 20 min. Then centrifuge to obtain the precipitate, mix it with water at a ratio of 1 g:20 mL, and then use saturated citric acid solution to adjust the pH of the mixture to 2, place it in a high pressure environment of 2.0 MPa, and treat it with ultrasound and microwave synergy for 10 min (microwave power: 500 W; ultrasonic power: 300 W), followed by magnetic stirring at 95°C for 2.5 h. After cooling, the mixture was dialyzed in a 3.5 KDa dialysis bag for 48 h, and then the dialyzed mixture was concentrated to 150 mL. The concentrated mixed solution was ultrasonically treated at 300 W for 5 min to form a pectin-cellulose composite film-forming slurry, which was then magnetically stirred until completely uniform. After degassing, it was poured onto a glass plate of appropriate size (slurry thickness was about 0.5 cm), dried at room temperature, and the film was peeled off.
[0029] Example 6 A method for preparing pectin-cellulose composite bioplastic based on fruit peel waste comprises the following steps: Select citrus peel, wash and dry it, and crush it through a 200 mesh sieve to obtain citrus peel powder. Weigh 10 g of citrus peel powder, mix it with water at a ratio of 1 g:20 mL, add 15 mg of hemicellulase (≥200 unit / mg solid), and incubate it at 40°C in a water bath constant temperature oscillator for 20 min. Then centrifuge to obtain the precipitate, mix it with water at a ratio of 1 g:20 mL, and then use saturated citric acid solution to adjust the pH of the mixture to 2, place it in a high pressure environment of 2.0 MPa, and treat it with ultrasound and microwave synergy for 10 min (microwave power: 500 W; ultrasonic power: 300 W), followed by magnetic stirring at 80°C for 4.0 h. After cooling, the mixture was dialyzed in a 3.5 KDa dialysis bag for 48 h, and then the dialyzed mixture was concentrated to 100 mL. The concentrated mixed solution was ultrasonically treated at 300 W for 5 min to form a pectin-cellulose composite film-forming slurry, which was then magnetically stirred until completely uniform. After degassing, it was poured onto a glass plate of appropriate size (slurry thickness was about 0.5 cm), dried at room temperature, and the film was peeled off.
[0030] Example 7 A method for preparing pectin-cellulose composite bioplastic based on fruit peel waste comprises the following steps: Select citrus peel, wash and dry it, and crush it through a 200 mesh sieve to obtain citrus peel powder. Weigh 10 g of citrus peel powder, mix it with water at a ratio of 1 g:30 mL, add 25 mg of hemicellulase (≥200 unit / mg solid), and incubate it at 45°C in a water bath constant temperature oscillator for 20 min. Then centrifuge to obtain the precipitate, mix it with water at a ratio of 1 g:20 mL, and then use saturated citric acid solution to adjust the pH of the mixture to 2, place it in a high pressure environment of 2.0 MPa, and treat it with ultrasound and microwave synergy for 10 min (microwave power: 500 W; ultrasonic power: 300 W), followed by magnetic stirring at 95°C for 2.5 h. After cooling, the mixture was dialyzed in a 3.5 KDa dialysis bag for 48 h, and then the dialyzed mixture was concentrated to 100 mL. The concentrated mixed solution was ultrasonically treated at 300 W for 5 min to form a pectin-cellulose composite film-forming slurry, which was then magnetically stirred until completely uniform. After degassing, it was poured onto a glass plate of appropriate size (slurry thickness was about 0.5 cm), dried at room temperature, and the film was peeled off.
[0031] Example 8 A method for preparing pectin-cellulose composite bioplastic based on fruit peel waste comprises the following steps: Hami melon peel was selected, washed and dried, and crushed through a 200-mesh sieve to obtain Hami melon peel powder. 10 g of peel powder was weighed, mixed with water at a ratio of 1 g:20 mL, 15 mg of hemicellulase (≥200 unit / mg solid) was added, and incubated at 40°C in a water bath constant temperature oscillator for 20 min. Then the precipitate was centrifuged and mixed with water at a ratio of 1 g:20 mL, and then the pH of the mixture was adjusted to 2 with a saturated citric acid solution, placed in a high pressure environment of 2.0 MPa, and ultrasonic microwave synergistically treated for 10 min (microwave power: 500 W; ultrasonic power: 300 W) and then magnetically stirred at 95°C for 2.5 h. After cooling, the mixture was dialyzed in a 3.5 KDa dialysis bag for 48 h, and then the dialyzed mixture was concentrated to 100 mL. The concentrated mixed solution was ultrasonically treated at 300 W for 5 min to form a pectin-cellulose composite film-forming slurry, which was then magnetically stirred until completely uniform. After degassing, it was poured onto a glass plate of appropriate size (slurry thickness was about 0.5 cm), dried at room temperature, and the film was peeled off.
[0032] Example 9 A method for preparing pectin-cellulose composite bioplastic based on fruit peel waste comprises the following steps: Select apple pomace, wash and dry it, and crush it through a 200-mesh sieve to obtain apple pomace powder. Weigh 10 g of peel powder, mix it with water at a ratio of 1 g:20 mL, add 15 mg of hemicellulase (≥200 unit / mg solid), and incubate it at 40°C in a water bath constant temperature oscillator for 20 min. Then centrifuge to obtain the precipitate, mix it with water at a ratio of 1 g:20 mL, and then use saturated citric acid solution to adjust the pH of the mixture to 2, place it in a high pressure environment of 2.0 MPa, and treat it with ultrasound and microwave for 10 min (microwave power: 500 W; ultrasonic power: 300 W), followed by magnetic stirring at 95°C for 2.5 h. After cooling, the mixture was dialyzed in a 3.5KDa dialysis bag for 48 h, and then the dialyzed mixture was concentrated to 100 mL. The concentrated mixed solution was ultrasonically treated at 300 W for 5 min to form a pectin-cellulose composite film-forming slurry, which was then magnetically stirred until completely uniform. After degassing, it was poured onto a glass plate of appropriate size (slurry thickness was about 0.5 cm), dried at room temperature, and the film was peeled off.
[0033] Example 10 A method for preparing pectin-cellulose composite bioplastic based on fruit peel waste comprises the following steps: Select pineapple peel, wash and dry it, crush it through a 200 mesh sieve to obtain pineapple peel powder. Weigh 10 g of peel powder, mix it with water at a ratio of 1g:20 mL, add 15 mg of hemicellulase (≥200 unit / mg solid), and incubate it at 40°C in a water bath constant temperature oscillator for 20 min. Then centrifuge to get the precipitate, mix it with water at a ratio of 1 g:20 mL, and then use saturated citric acid solution to adjust the pH of the mixture to 2, place it in a high pressure environment of 2.0 MPa, and treat it with ultrasound and microwave synergy for 10 min (microwave power: 500 W; ultrasonic power: 300 W), followed by magnetic stirring at 95°C for 2.5 h. After cooling, the mixture was dialyzed in a 3.5KDa dialysis bag for 48 h, and then the dialyzed mixture was concentrated to 100 mL. The concentrated mixed solution was ultrasonically treated at 300 W for 5 min to form a pectin-cellulose composite film-forming slurry, which was then magnetically stirred until completely uniform. After degassing, it was poured onto a glass plate of appropriate size (slurry thickness was about 0.5 cm), dried at room temperature, and the film was peeled off.
[0034] Example 11 A method for preparing pectin-cellulose composite bioplastic based on fruit peel waste, comprising the following steps: Watermelon peel was selected, washed and dried, and crushed through a 200-mesh sieve to obtain watermelon peel powder. 10 g of peel powder was weighed, mixed with water at a ratio of 1 g: 20 mL, 15 mg of hemicellulase (≥ 200 unit / mg solid) was added, and incubated at 40 ° C in a water bath constant temperature oscillator for 20 min. Then the precipitate was centrifuged and mixed with water at a ratio of 1 g: 20 mL, and then the pH of the mixture was adjusted to 2 with saturated citric acid solution, placed in a high pressure environment of 2.0 MPa, and ultrasonic microwave synergistic treatment for 10 min (microwave power: 500 W; ultrasonic power: 300 W) and then magnetically stirred at 95 ° C for 2.5 h. After cooling, the mixture was dialyzed in a 3.5KDa dialysis bag for 48 h, and then the dialyzed mixture was concentrated to 100 mL. The concentrated mixed solution was ultrasonically treated at 300 W for 5 min to form a pectin-cellulose composite film-forming slurry, which was then magnetically stirred until completely uniform. After degassing, it was poured onto a glass plate of appropriate size (slurry thickness was about 0.5 cm), dried at room temperature, and the film was peeled off.
[0035] Comparative Example 1 A method for preparing pectin-cellulose composite bioplastic based on peel waste comprises the following steps: Select citrus peel, wash and dry it, and crush it through a 200-mesh sieve to obtain citrus peel powder. Weigh 10 g of citrus peel powder, mix it with water at a ratio of 1 g:20 mL, add 15 mg of hemicellulase (≥200 unit / mg solid), and incubate it at 40°C in a water bath constant temperature oscillator for 20 min. Then centrifuge to obtain the precipitate, mix it with water at a ratio of 1 g:20 mL, and then use hydrochloric acid to adjust the pH of the mixture to 2, place it in a high pressure environment of 2.0 MPa, and treat it with ultrasound and microwave synergy for 10 min (microwave power: 500W; ultrasonic power: 300 W), followed by magnetic stirring at 95°C for 2.5 h. After cooling, the mixture was dialyzed in a 3.5 KDa dialysis bag for 48 h, and then the dialyzed mixture was concentrated to 100 mL. The concentrated mixed solution was ultrasonically treated at 300 W for 5 min to form a pectin-cellulose composite film-forming slurry, which was then magnetically stirred until completely uniform, degassed and poured onto a glass plate of appropriate size (slurry thickness was about 0.5 cm), and dried at room temperature. Since hydrochloric acid cannot play the cross-linking role of citric acid, a complete film material cannot be obtained without the addition of other cross-linking agents or plasticizers.
[0036] Comparative Example 2 A method for preparing pectin-cellulose composite bioplastic based on peel waste comprises the following steps: Select citrus peel, wash and dry it, and crush it through a 200 mesh sieve to obtain citrus peel powder. Weigh 10 g of citrus peel powder, mix it with water at a ratio of 1 g:20 mL, add 15 mg of hemicellulase (≥200 unit / mg solid), and incubate it at 40°C in a water bath constant temperature oscillator for 20 min. Then centrifuge to obtain the precipitate, mix it with water at a ratio of 1 g:20 mL, and then use saturated citric acid solution to adjust the pH of the mixture to 2, place it in a high pressure environment of 2.0 MPa, and treat it with ultrasound and microwave for 10 min (microwave power: 500 W; ultrasonic power: 300 W) and then stir it magnetically at 95°C for 2.5 h. After cooling, the mixture was dialyzed in a 3.5 KDa dialysis bag for 48 h. The dialyzed mixture was ultrasonically treated at 300 W for 5 min to form a pectin-cellulose composite membrane slurry, which was then magnetically stirred until completely uniform, degassed and poured onto a glass plate of appropriate size (slurry thickness is about 0.5 cm), and dried at room temperature. Since the slurry has not undergone a concentration step, the pectin-cellulose composite content in the slurry is very low, so the film-forming stability is poor or it is difficult to form a complete film.
[0037] Comparative Example 3 A method for preparing pectin-cellulose composite bioplastic based on peel waste comprises the following steps: Select citrus peel, wash and dry it, and crush it through a 200 mesh sieve to obtain citrus peel powder. Weigh 10 g of citrus peel powder, mix it with water at a ratio of 1 g:20 mL, add 15 mg of hemicellulase (≥200 unit / mg solid), and incubate it at 40°C in a water bath constant temperature oscillator for 20 min. Then centrifuge to obtain the precipitate, mix it with water at a ratio of 1 g:20 mL, place it in a high pressure environment of 2.0 MPa, and treat it with ultrasonic microwave synergy for 10 min (microwave power: 500 W; ultrasonic power: 300 W), followed by magnetic stirring at 95°C for 2.5 h. After cooling, the mixed solution was dialyzed in a 3.5 KDa dialysis bag for 48 h, and then the dialyzed mixed solution was concentrated to 100 mL. The concentrated mixed solution was ultrasonically treated at 300 W for 5 min to form a pectin-cellulose composite film-forming slurry, which was then magnetically stirred until completely uniform, degassed and poured onto a glass plate of appropriate size (slurry thickness is about 0.5 cm), and dried at room temperature. Due to the lack of acid treatment, it is difficult to dissolve the pectin in the peel into the solution, and it is difficult to complete the separation of pectin and cellulose. Therefore, it is difficult to form a film.
[0038] The preparation schemes of Comparative Examples 1-3 above are all difficult to form a complete film.
[0039] Experimental example The mechanical properties were measured by cutting the membrane into 100 mm × 50 mm rectangles and measuring its tensile strength using an automatic tensile testing machine with an initial clamping distance and speed of 50 mm and 1 mm / s, respectively. The test results are shown in Table 1.
[0040] Table 1 is a performance comparison of the bioplastic prepared in Example 1 and commercially available cling film (PVC) tensile strength Biological toxicity Degradable Recyclable Example 1 46.3 MPa none Degradation in 1 month Can be recycled Commercially available plastic wrap 10.15 MPa Known potential hazards of micro-nanoplastics none none Figure 2 The paper shows the production of fruit peel waste, the formation mechanism of bioplastics, the performance comparison with other plastics, and the schematic diagram of large-scale production. A large amount of fruit peel waste is generated every year around the world, such as kiwi, banana, pineapple, apple, watermelon and citrus peels ( Figure 2 a) (M in the figure is million tons, HM is billion tons). In the present invention, we separated pectin and cellulose in the cell wall of the fruit peel and then self-assembled them in situ to form pectin-cellulose composite bioplastics. In this process, citric acid acts as a bridge, allowing pectin and cellulose to form a stable structure similar to a carboxylic acid dimer ( Figure 2 b). Comparing the common properties of bioplastics with some other plastics, the prepared bioplastics have shown obvious advantages in five aspects: sustainability, cost, mechanical properties, eco-friendliness and human health ( Figure 2 c). The inventors also explored the possibility of large-scale production under this process condition, and it can be seen that it is possible to achieve mass production ( Figure 2 d).
[0041] Figure 3 The mechanism of the formation process of pectin-cellulose composite bioplastics is shown. It can be seen that the binding energy of the most stable adduct geometry between pectin, cellulose and citric acid predicted by DFT is ∆G = -32.0 kcal / mol ( Figure 3 a). Pectin and cellulose are stably cross-linked by hydrogen bonds under the action of citric acid. Therefore, based on the DFT results, they finally form a stable carboxylic acid dimer structure ( Figure 3 b).
[0042] Figure 4 The images show the load-bearing, plasticity and folding of the bioplastic prepared in Example 1. It can be seen that a very small size of bioplastic can bear a weight of 1 kg ( Figure 4 a), and it will not break after being folded arbitrarily, which corresponds to its high mechanical properties. Figure 4 b and 4c show its arbitrary folding images, indicating its excellent flexibility.
[0043] Figure 5The applicability of the process used in the present invention to other fruit peels is demonstrated. It can be seen that the process provided by the present invention can be used to treat watermelon peel ( Figure 5 a) Pineapple peel ( Figure 5 b) Apple pomace ( Figure 5 c) and cantaloupe rind ( Figure 5 d) conversion into bioplastics. Therefore, this process is applicable to most fruit peels rich in pectin and cellulose.
[0044] Figure 6 The plasticity and processability of the bioplastic prepared in Example 1 are demonstrated. Under the action of water, broken bioplastics can be welded together. They can also be processed into other shapes, such as straws. Based on this characteristic, we crushed the bioplastics and used water as a medium to verify their reprocessable properties. Under the action of water, the structure formed between pectin, cellulose and citric acid began to loosen and break, and with drying and loss of water, they can be reordered and formed into a stable structure. Therefore, the bioplastics exhibit water plasticity and processability.
[0045] Figure 7 The cytotoxicity results of the bioplastics prepared in Example 1 are shown. It can be seen that the cell survival rate of the bioplastics after 48 hours is still maintained at a very high level (>85%), showing excellent biosafety. Therefore, these bioplastics are biosafe, and the bioplastics are derived from natural non-toxic plants or edible food raw materials. This biosafety is particularly conducive to its application in the field of food packaging.
[0046] Figure 8 The bioplastic prepared in Example 1 is shown to be degradable. The commonly available PVA plastic is used as a control. It can be seen that whether buried in the soil or thrown into the natural environment, they can be degraded in a very short time. However, commercially available plastics are difficult to degrade, which shows the advantages of the bioplastic provided in this application in terms of environmental friendliness.
[0047] The present invention makes maximum use of the peel waste, not only avoiding its damage to the environment and ecology, but also improving the application value of the peel waste; it has the properties of biosafety, degradability, processability and recyclability, and has great potential to replace petrochemical plastic products (especially in the field of food packaging).
[0048] The above embodiments are preferred implementations of the present invention, which mainly demonstrate and describe the main features and basic principles of the present invention. However, the implementation of the present invention is not limited to the above embodiments, and any modification, alteration, substitution, combination, simplification made by any person familiar with the relevant fields and technologies without departing from the spirit and scope of the present invention shall be deemed to be within the scope of the present invention.
Claims
1. A method for preparing pectin-cellulose composite bioplastics based on peel waste, characterized in that: The following steps are involved: 1) Dry and crush the peel; 2) Mix the peel powder with water, perform enzymatic hydrolysis, and centrifuge to obtain the precipitate; 3) mixing the precipitate obtained in step 2) with water, adjusting the pH to 1.8-2.2 with a saturated citric acid solution, breaking the cell wall under high pressure, and then magnetically stirring at 65-95°C for 2-4 h; 4) cooling the mixture obtained in step 3), and placing it in a dialysis bag for dialysis; 5) concentrating the dialyzed mixed solution obtained in step 4), dispersing by ultrasonication, and stirring until uniform to obtain a pectin-cellulose composite film-forming slurry; 6) Degas the slurry obtained in step 5), pour it evenly onto a glass plate, evaporate the water at room temperature, and peel it off to obtain bioplastic.
2. The method for preparing pectin-cellulose composite bioplastic based on peel waste according to claim 1, characterized in that: In step 1), the peel is crushed and then passed through a 200-mesh sieve, and the peel is selected from one of citrus peel, watermelon peel, cantaloupe peel, pineapple peel, apple peel and residue.
3. According to the method for preparing pectin-cellulose composite bioplastics based on peel waste as described in claim 1, in step 2), peel powder is mixed with water in a ratio of 1 g: 15-30 mL; the enzyme used is hemicellulase, and the hemicellulase activity is ≥200 unit / mg solid, the amount of enzyme added accounts for 0.15%-0.25% of the peel mass, and the enzymatic hydrolysis treatment is an oscillation treatment at 40°C for 15-30 minutes, followed by centrifugation at 5000-6000rpm to obtain the precipitate.
4. The method for preparing pectin-cellulose composite bioplastic based on peel waste according to claim 1, characterized in that: The pressure of the high pressure environment in step 3) is 2.0-3.0 MPa.
5. The method for preparing pectin-cellulose composite bioplastic based on peel waste according to claim 1, characterized in that: In step 3), the precipitate is mixed with water at a ratio of 1 g: 15-30 mL, and then a saturated citric acid solution is used to adjust the pH to 1.8-2.2; the cell wall breaking treatment is an ultrasonic-microwave synergistic treatment, the microwave power is 200-500 W, the ultrasonic power is 200-400 W, and the treatment time is 10-20 min.
6. The method for preparing pectin-cellulose composite bioplastic based on peel waste according to claim 1, characterized in that: In step 4), the molecular cutoff of the dialysis bag is 3.5-6.0 KDa, and the dialysis time is 24-48 hours.
7. The method for preparing pectin-cellulose composite bioplastic based on peel waste according to claim 1, characterized in that: Every 10 g of the peel material in step 1) is concentrated to 100 mL in step 5).
8. The method for preparing pectin-cellulose composite bioplastics based on peel waste according to claim 1, characterized in that: In step 5), the ultrasonic power of the ultrasonic dispersion is 200-500 W, the ultrasonic time is 5-10 min, and then magnetic stirring is performed until it is completely uniform.
9. The method for preparing pectin-cellulose composite bioplastic based on peel waste according to claim 1, characterized in that: In step 6), the vacuum degree during degassing is -0.1 MPa, and the slurry is spread on a glass plate with a thickness of 0.3-0.5 cm. The drying condition is to evaporate the water naturally at room temperature, and then peel it off to obtain the bioplastic.
10. Pectin-cellulose composite bioplastic prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing edible film rich in hawthorn pectin and gelatin
CN110724289A
Method for extracting pectin, hemicellulose and cellulose from citrus peels and application
CN116948053A
Technology for extracting citrus reiculata peel pectin through ultrasonic-assisted enzyme method
CN117186265A
Method for resource utilization of fruit peel waste
CN117777318A
Biodegradable plastic based on fruit waste powder mixture
WO2012078021A1